At war with PTSD battling post traumatic stress disorder with virtual reality - McLay, Robert N. (Johns Hopkins University Press, 2012)
Shell shock, combat fatigue, Vietnam Syndrome--whatever the name, post traumatic stress disorder (PTSD) has been with us since ancient Greece. With 20 percent of the veterans of Afghanistan and Iraq exhibiting PTSD symptoms, the United States military has a strong interest in combating the condition. Several years into the project, McLay recounts openly and with bleak honesty the successes, failures, and limits of virtual reality treatment--but his experiences hold out hope.